2001
DOI: 10.1021/bc000153b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Substituted Ligands for the Peroxisome Proliferator-Activated Receptor Gamma (PPARγ):  Potential Imaging Agents for Metastatic Tumors

Abstract: The peroxisome proliferator-activated receptor gamma (PPARgamma), a primary regulator of lipid metabolism, is present in many tumor cell lines and animal tumor systems and, in some cases, can mediate effective antitumor therapy with potent synthetic ligands. In an approach to image tumors with positron-emission tomography (PET) based on their content of PPARgamma, we have synthesized two fluorine-substituted analogues of a high affinity ligand from the phenylpropanoic acid class. The analogue having the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Kim et al suggested a new approach for PET oncology in chosing the peroxisome proliferator-activated receptor Á (PPARÁ) as target for tracer devlopment (44). This receptor was found in many in vitro and in vivo tumour models.…”
Section: -------------------------------------------------mentioning
confidence: 99%
“…Kim et al suggested a new approach for PET oncology in chosing the peroxisome proliferator-activated receptor Á (PPARÁ) as target for tracer devlopment (44). This receptor was found in many in vitro and in vivo tumour models.…”
Section: -------------------------------------------------mentioning
confidence: 99%
“…To develop agents for imaging PPARγ by positron emission tomography (PET), our group initially evaluated two fluorine-18 labeled PPARγ receptor ligands based on the known 2-alkoxy-3-phenylpropanoic acid PPARγ ligand, SB 213 068 [13]. Tissue distribution studies of these compounds, however, did not show evidence of receptor-mediated uptake in brown fat, the most receptor-rich tissue [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…With this goal in mind, some time ago our group evaluated as PET imaging agents a set of fluorine-18 labeled PPARγ receptor ligands, based on the known compound SB 213068 (Scheme 1) (17). The binding of these fluorine-substituted compounds was selective for PPARγ compared to the PPARR and PPARδ subtypes; however, their affinity for PPARγ, though good, was not in the low nanomolar region as would be desirable for in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of these fluorine-substituted compounds was selective for PPARγ compared to the PPARR and PPARδ subtypes; however, their affinity for PPARγ, though good, was not in the low nanomolar region as would be desirable for in vivo imaging. Also, one SB 213068 analogue (5), prepared in the fluorine-18 labeled form (17), did not show evidence of receptor-mediated uptake in tissue distribution studies in brown fat, the most receptor-rich tissue (18).…”
Section: Introductionmentioning
confidence: 99%